Identification of avobenzone by-products formed by various disinfectants in different types of swimming pool waters. (April 2020) - Lebedev, Albert T.; Bavcon Kralj, Mojca; Polyakova, Olga V.; Detenchuk, Elena A.; Pokryshkin, Sergey A.; Trebše, Polonca
Graphical abstract: Highlights: Avobenzone aquatic halogenation led to formation of over 60 DBPs. The presence of Br − and I − led to formation of brominated and iodinated avobenzone DBPs. Chlorination into aromatic ring proceeds only with intermediate DBPs. Sunscreen formulation influences on degradability of avobenzone. Aquatic chlorination of avobenzone formulations led to the increase in toxicity. Abstract: The increased use of sunscreens and other cosmetics containing UV filters causes human and environmental burden. Avobenzone is a widely used UV filter. In its pure form it is known to undergo several transformations including photo-isomerisation, photodegradation, and halogenation. Over 60 disinfection by-products were identified as transformation products of avobenzone in different disinfection reactions of chlorination and bromination in fresh and seawater. Two occasional samples of swimming pool water demonstrated the presence of some of these by-products at noticeable levels as judged by GC-MS peak areas. Although the toxicity of the majority of these products remain unknown, chlorinated phenols and acetophenones are known to be rather toxic. Aquatic bromination of avobenzone resulted in the identification of 33 disinfection by-products (DBPs). Many of them contain bromine in the molecular structure. Addition of copper salt slightly decreases conversion rate simultaneously increasing the levels of major brominated products. Photostability of 3 commercial sunscreen products (solar protection factor 30) containing avobenzone was studied under different experimental conditions including UVA/UVB, UVC photostimulation and chlorination. The commercial sunscreen products have completely different enhancing and inhibitory effect on avobenzone degradation under UVC light. The complex composition of commercial products caused also a protective shield in case of chlorinated solutions of commercial formulations exposed to chlorine and UVA/UVB light at the same time.